Effect of Zinc Source and Level on Growth Performance, Fecal Dry Matter, and Fecal Zinc Concentration of Nursery Pigs - Julian Arroyave; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Katelyn N. Gaffield; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 2,268 pigs (initially 12.5 ± 0.68 lb) were used to evaluate the effect of zinc (Zn) sources and levels on nursery performance and fecal dry matter. At weaning, pens of pigs were sorted by body weight (BW) and then randomly assigned to one of the seven dietary treatments in a 3 × 2 + 1 arrangement, with main effects of Zn source and level. The Zn sources included zinc oxide (ZnO) and two sources of Zn hydroxychloride. The total dietary Zn levels were set at 1,500 ppm or 1,000 ppm during phase 1 and at 1,000 ppm or 500 ppm during phase 2. An additional treatment was included as a positive control, utilizing 3,000 and 2,000 ppm of Zn from ZnO in phases 1 and 2, respectively. After the experimental period (dietary phases 1 and 2), all pigs were fed a common phase 3 diet for 14 d, which contained 100 ppm of added Zn from ZnSO4. On d 7 and 21, fecal samples from three pigs per pen were collected for dry matter analysis. During the experimental phase, common phase, and overall, no significant Zn source × level interactions or main effects of Zn source or level were observed. Within the diets provided Zn from ZnO, no differences were observed between treatments for growth performance, mortality, removals, and fecal dry matter. For the d 7 fecal Zn concentration, a significant interaction (P = 0.009) between the Zn source × level was observed, where a greater (P < 0.05) fecal Zn concentration was observed as the dietary Zn inclusion increased when ZnO or Zn hydroxychloride source B was used, but no differences (P > 0.10) between levels were observed in the Zn hydroxychloride source A. At d 21, the fecal Zn concentration decreased (P < 0.001) as dietary Zn concentration decreased, independent of the Zn source (P > 0.10). In conclusion, the source and level of dietary Zn did not significantly impact growth performance, removals, mortality, or fecal dry matter of nursery pigs. However, utilizing lower dietary Zn levels independent of the source resulted in lower fecal Zn concentration.
Keywords: dietary zinc; growth performance; zinc excretion; zinc oxide; zinc hydroxychloride